Progress and Perspective of Metallic Glasses for Energy Conversion and Storage. Issue 8 (18th January 2022) - Jiang, Rui; Da, Yumin; Chen, Zelin; Cui, Xiaoya; Han, Xiaopeng; Ke, Haibo; Liu, Yanhui; Chen, Yanan; Deng, Yida; Hu, Wenbin
Abstract: Owing to its unique atomic arrangement and electronic structure, metallic glass (MG) has been widely investigated in the field of energy storage and conversion. In the past few decades, multiple strategies have been developed to synthesize bulk and nanosized MG based materials. Here, combining the structure–activity relationship of MG with electrochemical reaction kinetics, the substantial progress of glass structures in electrocatalytic processes are highlighted, including the hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, methanol oxidation reaction, carbon dioxide reduction reaction, and nitrogen fixation. Meanwhile, applications of MG materials in energy storage devices, like supercapacitors and lithium‐ion batteries, are also introduced in detail. Finally, challenges and possibilities for reasonable design of highly‐efficient MG‐based electrode materials are proposed. The integration of high‐throughput methods, artificial intelligence technology, as well as advanced characterization techniques is fundamental to screen materials with remarkable performance. This review aims to deepen the understanding of the relationship between electronic structure and electrochemical performance, providing guidance for rational design of functional MG materials with outstanding activity, selectivity, and durability. Abstract : Metallic glass (MG) has been widely investigated in the field of energy storage and conversion. Herein, the advantages and synthetic strategies of MG‐based catalysts are summarized. Combined with the structure–activity relationship and electrochemical kinetic behaviors of MG, the critical role of the glass structure in electrochemical processes is highlighted. Based on high‐throughput screening and machine learning, challenges and possible development directions of MGs are emphasized.